A2.16 Synovial Fluid Neutrophils Undergoing Netosis Contribute to Joint Inflammation by Producing Citrullinated Autoantigens. (25th February 2013) - Spengler, Julia; Lugonja, Bozo; Creese, Andrew; Nicholas, Anthony; Milward, Mike; Pearson, Mark; Buckley, Christopher D; Filer, Andrew; Raza, Karim; Cooper, Paul R; Chapple, Iain LC; Scheel-Toellner, Dagmar
Abstract : Objectives: Anti-citrullinated protein antibodies (ACPA) are characteristically detected in patients with rheumatoid arthritis (RA) and growing evidence suggests that they are involved in disease pathogenesis. During disease flares large numbers of neutrophils enter the joint space of RA patients. These cells can extrude genomic DNA in an active process termed NETosis. NETosis critically depends on histone citrullination by peptidyl deiminase 4 (PAD4). Here we tested the hypothesis that activation and release of PAD4 during NETosis contributes to the production of autoantigens in the inflamed joint. Materials and Methods: Levels of extracellular DNA in the synovial fluid (SF) of patients with RA (n = 23) and osteoarthritis (OA) (n = 15) or crystal arthritis (n = 6) were quantified using the non cell-permeable DNA dye SYTOX Green. PAD4, neutrophil elastase, citrullinated proteins and bound human IgG were labelled in association with DNA on smear preparations of RA SF and detected by immunofluorescence. NETs from SF and in vitro stimulated neutrophils were isolated and western blotting and mass spectrometry were used to identify proteins released during NET formation and proteins co-fractionated with NETs. PAD enzymatic activity was determined after NETosis in vitro and in the SF of patients with RA (n = 9) and OA (n = 9). Results: Extracellular DNA was detected in SF from patients with RA and crystal arthritis at significantly higher levels than in OA SF (RA versus OA p < 0.0001). Association of neutrophil elastase with decondensed DNA both on smear preparations and in NETs isolated from RA SF suggests that the extracellular DNA is derived from NETosis. On smear preparations PAD4 co-localised with decondensed chromatin in the SF of RA patients. PAD2 and PAD4 are released into the supernatant of in vitro stimulated neutrophils and were detected in NET fractions isolated from RA SFs. PAD enzymatic activity was released from neutrophils during in vitro activated NETosis while PAD activity in SF from RA patients was significantly higher than in OA patients (p < 0.001). The products of PAD activity, citrullinated proteins, were released into the supernatant and co-fractionated with extracellular DNA during in vitro NETosis. Furthermore, citrullinated proteins and bound human immune complexes were detected on NETs isolated from RA SF. Conclusions: These findings suggest that neutrophil NETosis, as a source of extracellular activated PAD enzymes, is involved in the production of auto-antigens in the joints of RA patients. In ACPA positive patients the resulting immune complexes can contribute to the perpetuation of the inflammatory response.